(untitled) - Bahr, Candace (Hoboken, NJ, 2004)
Conversational book covers communicating with your partner about money, discovering your money style, learning the seven truths about women and money, taking control of spending and saving, tailoring investments, coping with divorce and widowhood, and more. DLC: Women--Finance, Personal.
Keywords: Women; Finance, personal